The state and education policy : the academies programme - Gunter, Helen (Continuum International Pub. Group, 2011)
The well-edited collection of papers by leading researchers and participants within a major reform process of the state and education system in particular. The shift from welfare based provision of public services to the quasi-market with private delivery and philanthropic investment is an issue that needs a thorough examination through evidence and rigorous argument. This book seeks to do this by not only charting events and providing detailed examination about what is happening but also by locating these developments within a contemporary political and social analytical framework. Topics cov.